International standards for neurological classification of spinal cord injury: impact of the revised worksheet (revision 02/13) on classification performance - Schuld, Christian; Franz, Steffen; Brüggemann, Karin; Heutehaus, Laura; Weidner, Norbert; Kirshblum, Steven C.; Rupp, Rüdiger (The journal of spinal cord medicine, 2016)
Comparison of the classification performance between the worksheet revisions of 2011 and 2013 of the International Standards for Neurological Classification of Spinal Cord Injury (ISNCSCI).
Gesehen am 26.05.2020